2007
DOI: 10.1103/physrevb.76.045419
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal flow in dielectrophoresis of single-walled carbon nanotubes

Abstract: We theoretically investigate the impact of the electrothermal flow on the dielectrophoretic separation of single-walled carbon nanotubes ͑SWNTs͒. The electrothermal flow is observed to control the motions of semiconducting SWNTs in a sizable domain near the electrodes under typical experimental conditions, therefore helping the dielectrophoretic force to attract semiconducting SWNTs in a broader range. Moreover, with the increase of the surfactant concentration, the electrothermal flow effect is enhanced, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Micropumps based on electrothermal flow have also been proposed by using an array of asymmetric pairs of electrodes25, 26. On the other hand, a combination of electrothermal flow and other electrokinetic effects have been demonstrated for particle trapping, concentration, separation, mixing, and pumping27-30. In addition to Joule heating induced electrothermal flow, opto-electrical fluid motion has been reported for particle manipulation31-33.…”
Section: Introductionmentioning
confidence: 99%
“…Micropumps based on electrothermal flow have also been proposed by using an array of asymmetric pairs of electrodes25, 26. On the other hand, a combination of electrothermal flow and other electrokinetic effects have been demonstrated for particle trapping, concentration, separation, mixing, and pumping27-30. In addition to Joule heating induced electrothermal flow, opto-electrical fluid motion has been reported for particle manipulation31-33.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our calculation suggests that by using the effective dipole moment method, the magnitude of the DEP force on SWNTs is very likely to be severely overestimated especially when they approach the electrodes such that their length becomes comparable to the length scale of the electric field. We have previously calculated DEP forces of SWNT by using the effective dipole moment method and compared its magnitude with the electrothermal force of the fluid, and concluded that the flow motions can dominate the motion of SWNTs in a sizable domain when applied voltage is high and when the concentration of solution is large [16]. The present work indicates that the domain where electrothermal flow is dominating can be even larger than we estimated since the effective dipole moment method overestimates the DEP force as SWNTs approaches to electrodes.…”
Section: Dep Force In a General External Electric Fieldmentioning
confidence: 98%
“…The reason is that either FEM or IBEM is used, the meshes based on which the numerical integrations are performed would inevitably possess large skewness; therefore, considerable numerical errors can occur. Another method is the point effective dipole method [3], which is used extensively for calculation of spherical and ellipsoidal-shaped cells and rod-shaped SWNTs [5,8,[11][12]16]. It is favored due to its simplicity, and becomes a practical approach.…”
mentioning
confidence: 99%
“…built on this by demonstrating with simulation and experiment that CNTs are preferentially attracted to already deposited not fully bridging CNTs forming chains, due to the enhanced electric field at CNT tips. [ 160b ] Oliva‐Avilés et al. reported additional experiments and simulations investigating the process of CNT chaining in dispersion during DEP.…”
Section: Patterning From Cnt Dispersionsmentioning
confidence: 99%